Panel 4: The Pathway and Effect of Digital Communication Technology (The Journal of Medicine, Humanity and Media, 2024)
Panel 4 of the 7th "Medicine, Humanities, and Media" International Academic Symposium focused on "The Pathway and Effect of Digital Communication Technology." Seven presenters from various institutions showcased their research, covering diverse topics in digital health communication. Key themes included e-cigarette prevention among adolescents, accessibility of visual news for the visually impaired, fertility health information avoidance among young women, media engagement and loneliness in empty-nest elderly, effectiveness of health communication for at-risk populations on Weibo, online health interventions for rural women, and non-suicidal self-injury behavior in adolescents. The presentations highlighted the multifaceted applications of digital communication technologies in addressing health issues across different demographics. Discussions emphasized the importance of tailored communication strategies, the role of intergenerational support in health literacy, and the need for more inclusive information dissemination. Reviewers praised the social relevance of the research while suggesting areas for theoretical development and methodological refinement. The panel underscored the significant impact of digital technologies on health communication and their potential to address various social and health challenges in the digital age.